Pengaruh Peran Aparat Pengawasan Intern Pemerintah (APIP) dan Kompetensi Aparatur Pemerintah Daerah terhadap Akuntabilitas Kinerja Instansi Pemerintah (AKIP) - Fenty Fajarwati; Silviana (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2025)
This study aims to examine the influence of the Role of APIP and the Competence of Local Government Apparatus on the implementation of Performance Accountability of Local Government Agencies in Garut Regency. A total of 67 respondents were involved in this study. Data testing was carried out using IBM SPSS 25 software. The results of the study indicate that the Role of Internal Government Supervisory Apparatus and the Competence possessed by Local Government Apparatus can improve the Performance Accountability of Government Agencies in Garut Regency. The existence of good accessibility also plays an important role in improving performance accountability in Garut Regency. Key word: Accountability Performance, Local Government, Internal Supervision, Performance, Competence